1969
DOI: 10.1080/0028825x.1969.10429101
|View full text |Cite
|
Sign up to set email alerts
|

The influence of growing temperature on photosynthesis and respiration of Pinus radiata seedlings

Abstract: Rates of photosynthesis at five light intensities and rates of respiration at fot:r temperatures, 9°, 16°, 24° and 30°e, were measured in three P. radiata seedling~ from each of the growing conditions IS°/10°, 24°/l9°, and 33°/28°c dly/night temperatures. Net photosynthesis at 30° and 9°c was reduced in seedlings grown u!1der the cold and the two warmer. preconditioning treatments respectively. ~Ixteen ~egrees appeared to be the optImum temnerature for net photosynthesis m seedlmgs grown at Iso/lO· and 24°/l9°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
52
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 7 publications
6
52
0
Order By: Relevance
“…Growth-temperature effects on Q 10 also appear to differ between plants exposed to a new thermal regime for several days and leaves and roots that develop under contrasting temperatures. Covey-Crump et al (2002) found that the Q 10 (between 15-23 • C) of Plantago lanceolata root R was greater at low measurement temperatures in plants exposed to 15 • C for 7 d than in plants kept at 23 • C. Similarly, Rook (1969) found that the Q 10 (between 15-30 • C) of leaf R in Pinus radiata seedlings grown at 33 / 28 • C increased following a 2-d exposure to 15 / 10 • C (rates of R measured at 15-30 • C increased significantly, whereas there was no change in R measured at 8 • C). Conversely, shifting of 15 / 10 • C grown plants to 33 / 28 • C resulted in the Q 10 decreasing within 2 d (again, no change in R at 8 • C was observed).…”
Section: Growth Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…Growth-temperature effects on Q 10 also appear to differ between plants exposed to a new thermal regime for several days and leaves and roots that develop under contrasting temperatures. Covey-Crump et al (2002) found that the Q 10 (between 15-23 • C) of Plantago lanceolata root R was greater at low measurement temperatures in plants exposed to 15 • C for 7 d than in plants kept at 23 • C. Similarly, Rook (1969) found that the Q 10 (between 15-30 • C) of leaf R in Pinus radiata seedlings grown at 33 / 28 • C increased following a 2-d exposure to 15 / 10 • C (rates of R measured at 15-30 • C increased significantly, whereas there was no change in R measured at 8 • C). Conversely, shifting of 15 / 10 • C grown plants to 33 / 28 • C resulted in the Q 10 decreasing within 2 d (again, no change in R at 8 • C was observed).…”
Section: Growth Temperaturementioning
confidence: 99%
“…1, where exposure of a warm-grown plant to the cold for several days results in an increase in the rate of R at a common measurement temperature (Rook 1969;Chabot and Billings 1972;Pisek et al 1973;Larigauderie and Körner 1995;Körner 1999;Atkin et al 2000b;Covey-Crump et al 2002;Zha et al 2002Zha et al , 2005Bolstad et al 2003). Conversely, exposure to high temperatures results in a decrease in the rate of R at a common temperature (Fig.…”
Section: Overviewmentioning
confidence: 99%
“…Acclimation may occur within a few days of a temperature change (Rook 1969;Billings et al 1971;Atkin et al 2000;Bolstad et al 2003;Lee et al 2005;Slot et al 2014a), but longer exposure to a new temperature may result in a greater degree of homeostasis (Smith and Hadley 1974). Longer exposure enables the plant to make a more complete thermal adjustment-for example, through changes in mitochondrial size and density in leaves (Armstrong et al 2006).…”
Section: Thermal Acclimation Of Leaf Dark Respirationmentioning
confidence: 99%
“…When normalized for plant cover, heated communities did indeed exhibit lower values for both CO 2 fluxes than did unheated communities, which is evidence for acclimation to elevated temperatures. Thermal acclimation of CO 2 fluxes was found in several other studies (Rook, 1969;Larigauderie and Körner, 1995;Loveys et al, 2003;Tjoelker et al, 1998;Atkin et al, 2006), although it did not occur in some studies on root respiration (Sowel and Spomer, 1986;Weger and Guy, 1991;Zogg et al, 1996;Burton and Pregitzer, 2003). Unfortunately, we could not partition our measured ecosystem respiratory fluxes into their autotrophic and heterotrophic components and therefore, we cannot state whether thermal acclimation of TER was due to decreased plant respiration, decreased heterotrophic respiration, or both.…”
Section: Heating Effectmentioning
confidence: 75%
“…Correspondence to: S. Vicca (sara.vicca@ua.ac.be) Although photosynthetic and respiratory rates increase with temperature (Larcher, 2003), both processes and their resulting CO 2 fluxes may also acclimate to warming conditions (Rook, 1969;Körner and Larcher, 1988;Bryla et al, 1997Bryla et al, , 2001Atkin et al, 2000aAtkin et al, , 2006Atkin and Tjoelker, 2003;King et al, 2006). Acclimation can be defined as the adjustment of processes such that plant performance is adapted to the new growth temperature (Lambers et al, 1998).…”
Section: Introductionmentioning
confidence: 99%